An Investigation into the Use of Ducktail at Transom Stern to Reduce Total Ship Resistance - Kurniawati, Fiqih Dwi; Pria Utama, I Ketut Aria (Institut Teknologi Sepuluh Nopember, 2017)
In this study it is aimed to investigate the application of ducktail at transom stern to reduce total resistance using Computational Fluid Dynamics (CFD). Ducktail is additional retrofit device to reduce effect of wetted transom causes wave and wake which cannot fully generate far away therefore absorbs energy. The method about saving energy possibilities was determined. The RANSE code CFX fitted with shear stress transport (SST) turbulence is used to carry out the simulation. Grid generator ICEM CFD is used to build hybrid grids for RANS code solvers. The result indicate ducktail reduce resistance significantly based on Froude numbers. The wave and wake fully transmitted into the far field. Ducktail becomes alternative appendages to increase energy efficiency.